2019
DOI: 10.1038/s41598-019-54873-w
|View full text |Cite
|
Sign up to set email alerts
|

RAG-2 deficiency results in fewer phosphorylated histone H2AX foci, but increased retinal ganglion cell death and altered axonal growth

Abstract: DNA double-strand breaks (DSBs), selectively visualized as γ-H2AX+ foci, occur during the development of the central nervous system, including the retina, although their origin and biological significance are poorly understood. Mutant mice with DSB repair mechanism defects exhibit increased numbers of γ-H2AX+ foci, increased cell death during neural development, and alterations in axonogenesis in the embryonic retina. The aim of this study was to identify putative sources of DSBs. One of the identified DSBs so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…The RAG1 gene has been derived from a Transib DNA transposon [ 286 ], and then its recombination activity was enhanced by the capture of a pro- RAG2 sequence [ 287 , 288 ]. In the context of the present review, it is interesting that RAG1 and RAG2 were shown to be expressed in neurons [ 289 , 290 , 291 ], even though the exact function of these recombinases in neurons is not clear.…”
Section: Mobile Genetic Elements In the Human Genome And Their Regula...mentioning
confidence: 99%
“…The RAG1 gene has been derived from a Transib DNA transposon [ 286 ], and then its recombination activity was enhanced by the capture of a pro- RAG2 sequence [ 287 , 288 ]. In the context of the present review, it is interesting that RAG1 and RAG2 were shown to be expressed in neurons [ 289 , 290 , 291 ], even though the exact function of these recombinases in neurons is not clear.…”
Section: Mobile Genetic Elements In the Human Genome And Their Regula...mentioning
confidence: 99%
“…We use Rag2/IL2rγ-deficient mice that also express human CSF1, which is crucial for the survival of xenografted human microglia (Hasselmann et al, 2019b). As previously reported, Rag2 is necessary for proper retinal development and Rag2 -/mice are blind (Alvarez-Lindo et al, 2019;Han et al, 2013). Thus, these Rag2 -/immunodeficient mice used in our study are likely not ideal for behavioral tests that require visual input.…”
Section: Limitations Of the Studymentioning
confidence: 83%
“…Interestingly, in RAG-2-deficient mice, γH2AX immunoreactive foci were less abundant in the retina, retinal ganglion cell death was increased, and axonal growth and navigation were impaired. All these features were common with those in mutant mice defective in DNA repair mechanisms [ 102 ].…”
Section: H2ax In the Normal Brainmentioning
confidence: 96%
“…In addition, a recent cytofluorimetric study has demonstrated that actively replicating neural progenitor cells harbor more DNA DSBs during early neurogenesis than at later differentiation stages [ 101 ]. Moreover, a study on mice lacking recombination activating 2 (RAG-2), a component of the RAG-1,2-complex responsible for initiating somatic recombination in lymphocytes, led to the identification of the long interspersed element-1 (LINE-1) retrotransposition as one of the sources of DSBs in retinal neurogenesis and to the suggestion that both DSBs generation and repair are genuine processes intrinsic to neural development [ 102 ]. Our understanding of the role of γH2AX in embryonic neurogenesis is made more complex by the concomitant occurrence of apoptosis during the generation of new neurons and glia.…”
Section: H2ax In the Normal Brainmentioning
confidence: 99%